Evaluating students achievement in using scratch 3.0 to develop program - Ang, Jie Qian (2023)
Scratch is an educational website widely adopted in education sectors to introduce the programming world to children aged between 8 to 16 years old. However, unlike existing IDE that comes with error detections, Scratch only provides a platform where Scratchers, the registered users on the Scratch website, creatively design their scripts and share their works with others. It does not come with an error detection function, contributing to a higher time consumption for educators to mark the scripts of the projects individually without the help of any system or machine. Fortunately, some existing tools such as Hairball and Dr. Scratch were developed to assist them in evaluating Scratch projects, but these tools still hold some limitations which might affect the accuracy of the evaluation results and negatively impact users’ experience and confidence level. Thus, this project focuses on developing a web application with ASP.NET core Razor Pages, which uses a novel evaluation method to evaluate Scratch projects by uploading the project onto the web application. This evaluation method considers the type of project to ensure fairness in assessing students’ performance. By logging into the web application, users will be given different privileges while accessing the web application, and a database will be utilised to store and retrieve users’ evaluation results based on their user privileges.